2004
DOI: 10.1080/14764170410029022
|View full text |Cite
|
Sign up to set email alerts
|

Effective epilation of white and blond hair using combined radiofrequency and optical energy

Abstract: Combined radiofrequency and optical energy technology may produce effective photoepilation of blond and white hair phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 17 publications
3
45
0
1
Order By: Relevance
“…The first study consisted of 40 adult subjects with different skin types (Fitzpatrick's II-V) and various hair colors [13]. The second study included 36 adult women with overall lighter skin phenotypes (I-V) and blond or white facial hair [14]. In both studies, subjects received four treatments at 8-to 12-week intervals over a period of 9-12 months.…”
Section: Hair Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study consisted of 40 adult subjects with different skin types (Fitzpatrick's II-V) and various hair colors [13]. The second study included 36 adult women with overall lighter skin phenotypes (I-V) and blond or white facial hair [14]. In both studies, subjects received four treatments at 8-to 12-week intervals over a period of 9-12 months.…”
Section: Hair Removalmentioning
confidence: 99%
“…Mean Hair Removal Efficiency by Hair Color After Four Treatment Sessions (Month 18), Using Combined IPL and RF Energies With the Aurora DS System[13,14] …”
mentioning
confidence: 99%
“…215 As such, laser hair removal works optimally on patients with dark (high melanin content) hair and fair (low melanin content) skin, a condition that enhances the selective targeting of hair follicles, while sparing the skin. One active area of laser hair removal research concentrates on extending eligibility for laser hair removal to patients with light hair: Sadick and Laughlin 216 reported the use of combined intense pulsed light and RF energy in place of standard lasers for successful removal of white and blond hair, while Sand et al 217 attempted to supplement melanin before laser treatment using a liposome spray. Future laser hair removal studies will continue addressing the problem of removing light hair and will also seek solutions for emerging issues such as pain control, pediatric use, and paradoxical regrowth of hair after treatment.…”
Section: Laser Hair Removalmentioning
confidence: 99%
“…Because RF does not require a chromophore target, this was the first technology that studies have shown to be effective at treating light-colored hair, including white. 46,47 The efficacy is lower when treating light-colored hair, however.…”
Section: Nd:yagmentioning
confidence: 99%